Characterization of the Fetal Blood Transcriptome and Proteome in Maternal Anti‐Fetal Rejection: Evidence of a Distinct and Novel Type of Human Fetal Systemic Inflammatory Response. (30th July 2013) - Lee, JoonHo; Romero, Roberto; Chaiworapongsa, Tinnakorn; Dong, Zhong; Tarca, Adi L.; Xu, Yi; Chiang, Po Jen; Kusanovic, Juan Pedro; Hassan, Sonia S.; Yeo, Lami; Yoon, Bo Hyun; Than, Nandor Gabor; et al.
<x xml:space="preserve">Abstract</x> Background The human fetus is able to mount a systemic inflammatory response when exposed to microorganisms. This stereotypic response has been termed the 'fetal inflammatory response syndrome' (FIRS), defined as an elevation of fetal plasma interleukin‐6 (IL‐6). FIRS is frequently observed in patients whose preterm deliveries are associated with intra‐amniotic infection, acute inflammatory lesions of the placenta, and a high rate of neonatal morbidity. Recently, a novel form of fetal systemic inflammation, characterized by an elevation of fetal plasma CXCL10, has been identified in patients with placental lesions consistent with 'maternal anti‐fetal rejection'. These lesions include chronic chorioamnionitis, plasma cell deciduitis, and villitis of unknown etiology. In addition, positivity for human leukocyte antigen (HLA) panel‐reactive antibodies (PRA) in maternal sera can also be used to increase the index of suspicion for maternal anti‐fetal rejection. The purpose of this study was to determine (i) the frequency of pathologic lesions consistent with maternal anti‐fetal rejection in term and spontaneous preterm births; (ii) the fetal serum concentration of CXCL10 in patients with and without evidence of maternal anti‐fetal rejection; and (iii) the fetal blood transcriptome and proteome in cases with a fetal inflammatory response associated with maternal anti‐fetal rejection. Method of study Maternal and fetal sera were obtained from normal term (n = 150) and spontaneous preterm births (n = 150). A fetal inflammatory response associated with maternal anti‐fetal rejection was diagnosed when the patients met two or more of the following criteria: (i) presence of chronic placental inflammation; (ii) ≥80% of maternal HLA class I PRA positivity; and (iii) fetal serum CXCL10 concentration >75th percentile. Maternal HLA PRA was analyzed by flow cytometry. The concentrations of fetal CXCL10 and IL‐6 were determined by ELISA. Transcriptome analysis was undertaken after the extraction of total RNA from white blood cells with a whole‐genome DASL assay. Proteomic analysis of fetal serum was conducted by two‐dimensional difference gel electrophoresis. Differential gene expression was considered significant when there was a P < 0.01 and a fold‐change >1.5. Results (i) The frequency of placental lesions consistent with maternal anti‐fetal rejection was higher in patients with preterm deliveries than in those with term deliveries (56% versus 32%; P < 0.001); (ii) patients with spontaneous preterm births had a higher rate of maternal HLA PRA class I positivity than those who delivered at term (50% versus 32%; P = 0.002); (iii) fetuses born to mothers with positive maternal HLA PRA results had a higher median serum CXCL10 concentration than those with negative HLA PRA results (P < 0.001); (iv) the median serum CXCL10 concentration (but not IL‐6) was higher in fetuses with placental lesions associated with maternal anti‐fetal rejection than those without such lesions (P < 0.001); (v) a whole‐genome DASL assay of fetal blood RNA demonstrated differential expression of 128 genes between fetuses with and without lesions associated with maternal anti‐fetal rejection; and (vi) comparison of the fetal serum proteome demonstrated 20 proteins whose abundance differed between fetuses with and without lesions associated with maternal anti‐fetal rejection. Conclusion We describe a systemic inflammatory response in human fetuses born to mothers with evidence of maternal anti‐fetal rejection. The transcriptome and proteome of this novel type of fetal inflammatory response were different from that of FIRS type I (which is associated with acute infection/inflammation).